2014
DOI: 10.1371/journal.pbio.1001864
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Hydrolysis Inhibits Synaptic Transmission by Increasing pH Buffering in the Synaptic Cleft

Abstract: A slow mechanism of retinal synaptic inhibition involves hydrolysis of ATP released from pannexin 1 channels (from the tips of horizontal cell dendrites); the resulting protons and phosphates acidify the synaptic cleft, which inhibits neurotransmitter release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 67 publications
6
103
1
Order By: Relevance
“…Since sensory inputs to the CNS can be altered in Panx1 −/− mice, as shown recently for the retina (Kranz et al, 2013; Vroman et al, 2014), it was hypothesized that similar changes could be found in other sensory organs. In this study, we characterize the impact of genetic ablation of Panx1 in the olfactory system.…”
Section: Introductionmentioning
confidence: 80%
“…Since sensory inputs to the CNS can be altered in Panx1 −/− mice, as shown recently for the retina (Kranz et al, 2013; Vroman et al, 2014), it was hypothesized that similar changes could be found in other sensory organs. In this study, we characterize the impact of genetic ablation of Panx1 in the olfactory system.…”
Section: Introductionmentioning
confidence: 80%
“…For instance, it is interesting to see that drPanx1a is less sensitive to ATP. Recently, evidence has been obtained that retinal horizontal cells release ATP via drPanx1a channels [34]. ATP is hydrolyzed extracellularly leading to acidification of the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%
“…The observed pH dependent channel properties of Panx1 are of particular interest, since physiological pH changes are linked to processes such as development [41], neuronal activity [42,43], lateral inhibition in the outer retina [34,44,45] and the circadian clock [46]. Furthermore, pH-changes are highly relevant for pathological conditions like ischemia and epilepsy in vivo [47], and in experimental model systems [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Support for this hypothesis comes from studies of the mammalian retina in which HEPES, a strong proton buffer, was used to disrupt surround inhibition generated in the outer retina and from a recent study in which a genetically encoded pH indicator was expressed in zebrafish cones (Davenport et al 2008, Wang et al 2014). The second hypothesis is that hemichannels (i.e., pores formed by connexins—gap junction subunits—expressed only in the horizontal cell membrane) encourage current flow through the synaptic cleft in such a way as to hyperpolarize photoreceptors when horizontal cells depolarize (Thoreson & Mangel 2012, Vroman et al 2014). …”
Section: Lateral Inhibition Modifies Signaling By Vertical Excitatorymentioning
confidence: 99%